Picture This: A Call for Uniformity in the Sales Tax Treatment of Digital Photographs - DiSanto, Amanda S.; Loengrad, Phillipa S. (The Columbia Journal of Law & the Arts, 2012)
The United States isn’t “going digital”-it has already gone. The iPod has made digital music the norm. Amazon’s Kindle has been on the market only since 2007, and the company already sells more e-books than traditional books. U.S. consumers downloaded almost 1.6 million apps for their portable digital devices in 2010. Yet, these purchases are taxed only in approximately half of the states. But books and music are not the only art forms that are increasingly transmitted digitally. Photography has embraced the digital revolution perhaps more than any other industry. Digital photography has replaced the film camera, and almost all commercial photography transactions are done without the photographer ever printing an image. When selling a digital image, a photographer faces challenges beyond simply finding a buyer for his work. He must also deal with the financial components of the transaction. In order to ensure he complies with the taxation aspects of the sale, he must consult the tax codes of not only his state, but also any state to which he is sending the image to determine whether or not he is responsible for collecting sales tax. Tax statutes are often vague and do not specifically address the photographer’s situation. States may tax some, all or no digital transfers. The statutes may be vague, asserting that “specified digital products” are taxed but leaving the photographer to search to find out if photography is such a product. Photographers must not only look at the states’ statutes, but also any official rulings or advisory opinions that may interpret the statutes specifically as they apply to photographers. Often, these rulings are not posted in the same area on a webpage as the statute and are difficult to find. The photographer may call his state’s tax department, but will probably receive different answers depending on with whom he speaks. While photographers can hire tax practitioners or accountants to assist them, they often cannot afford to keep an expert on retainer to ask whether sales tax is incurred for each transaction into which they enter. When the myriad of state tax laws are inconsistent and unclear, the task becomes exponentially harder for individuals who run small businesses. This paper will argue that states should uniformly impose the same tax treatment on digital transfers of photographs as they do on transfers made through traditional methods, such as when a negative or print is sold. The current sales tax system costs both states and photographers time and money. States suffer lost revenue through uncollected sales tax and through the time that revenue department employees spend in addressing questions from the community in an attempt to clarify confusing and unnecessarily complex laws. Photographers, in turn, must either hire tax practitioners to sort out what taxes are owed or devote energies towards circumventing the tax laws. The current system is inefficient and should change to provide clarity and consistency among the states, creating a new regime where substance is taxed over form.